The awakening of the East : - Leroy-Beaulieu, Pierre (McClure, Phillips & CO., 1900)
This book is the result of personal observations made in the course of a journey through Siberia, China, and Japan, lasting over a year, and is supplemented by imformation derived chiefly from official and carefully collated documents